(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2018)
This study identifies communication and collaboration skills improvement of junior high school (SMP) students when learning physics using Integrated Multimedia-based Instruction (MBI2). In this one-shot case study, the subject was thirty-one eight grade students in one of the public schools in Bandung, West Java. Students’ communication and collaboration skills were evaluated by learning and laboratory activity observation. Results showed that communication and collaboration skills were improved with four meetings that suggested that MBI2 could improve junior high school students’ communication and collaboration skills. Abstrak Penelitian ini mengidentifikasi perbaikan keterampilan komunikasi dan kolaborasi siswa Sekolah Menengah Pertama (SMP) ketika belajar Fisika dengan menggunakan Integrated Multimedia-based Instruction (MBI2). Dalam one-shot case study ini, subjek adalah 31 siswa di salah satu sekolah negeri di Bandung, Jawa Barat. Keterampilan komunikasi dan kolaborasi siswa dievaluasi melalui observasi kegiatan pembelajaran dan praktikum. Hasil menunjukkan abhwa keterampilan komunikasi dan kolaborasi membaik dalam empat pertemuan yang mengimplikasikan bahwa MBI2 dapat memperbaiki keterampilan komunikasi dan kolaborasi siswa SMP.